2007
DOI: 10.1007/s10995-007-0227-y
|View full text |Cite
|
Sign up to set email alerts
|

Using Linked Data to Assess Patterns of Early Intervention (EI) Referral among Very Low Birth Weight Infants

Abstract: In MA, most infants born <1,200 g are referred to EI, but disparities exist. Analysis of linked population-based health and developmental services can inform programs in order to reduce disparities and improve access for all high-risk infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 33 publications
3
67
1
Order By: Relevance
“…First, consistent with results about EI referral in Massachusetts,13 enrollment in South Carolina was more likely among multiple-birth infants. Our findings also indicate that NMI V is independently correlated with enrollment; however, the heavier of these infants (750 to 999 g) were also more likely to be enrolled.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…First, consistent with results about EI referral in Massachusetts,13 enrollment in South Carolina was more likely among multiple-birth infants. Our findings also indicate that NMI V is independently correlated with enrollment; however, the heavier of these infants (750 to 999 g) were also more likely to be enrolled.…”
Section: Discussionsupporting
confidence: 79%
“…A study from Massachusetts that used linked data showed that 93% of infants born weighing <1200 g during 1998–2000 were referred to EI; however, the percentage enrolled was not reported 13. Another study showed that only 10% of children in the United States classified as having delays at 24 months received EI services; the latter study included all children born <1500g as well as other children who fit the criteria of delay 14…”
mentioning
confidence: 99%
“…17,25,26 Wang et al 20 reported higher EI enrollment among children with birth weights ,1000 g who were receiving public insurance. Results from our regression analyses also showed that EI referrals were positively associated with public insurance.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these risk factors are recognizable at the time of birth and recorded on birth or delivery hospitalization records. 14,15 Eligibility is determined by using an approved tool, the Battelle Developmental Inventory, Second Edition, or informed clinical opinion if the child does not meet the current definition of established condition or developmental delay when qualitative concerns can be documented. The most commonly used EI services include developmental specialists, occupational therapists, and speech and language pathologists.…”
Section: Data Sourcesmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] Children with these adverse outcomes are at increased risk of poor developmental and behavioral outcomes and are specifically in need of Early Intervention (EI) programs. [13][14][15][16] Cognitive, behavioral, and social outcomes can be improved if developmental/behavioral interventions are initiated early in life. 15,17,18 These beneficial and longlasting services can be provided through EI programs to children with developmental delays or at risk for such delays at no cost.…”
mentioning
confidence: 99%